The labor load in a socioeducative support center - descriptive study - Maristel KG Kasper Grando; Ana LCK Lúcia Cardoso Kirchhof; Carmem LCB Lúcia Colomé Beck; Letícia LT de Lima Trindade (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
The present research consisted of reconstructing the working process of monitors in a Social and Educative Support Center intended to care offender adolescents with the objective of identifying labor loads and diseases aiming at the workers' awareness and health promotion. It has been used the Italian Labor Model as methodological line for the analysis and interpretation of these workers' reality. The presuppositions of this model comprise a homogeneous group, subjectivity appraisal, non-delegation and consensual validation. The sampling involved seven monitors of the morning shift who participated of a collective interview. Results from the research evidenced that the most present loads in the labor environment have been both physical and psychic. Upon the study completion, the research enabled the identification of a high degree of psychic distress in the job evidenced by the absenteeism among other important findings.